2012
DOI: 10.1159/000338212
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of ‘Low-Grade Intraepithelial Lesion, Cannot Exclude High Grade’ Diagnosis: A Single Institution’s Experience

Abstract: Objective: Squamous intraepithelial lesions (SILs) are classified as low-grade SIL (LGSIL) and high-grade SIL (HGSIL). ‘LGSIL cannot exclude high grade’ (LGSIL-H) interpretive category has been used in cases where findings exceed criteria for LGSIL, but do not fulfill the criteria for HGSIL. This study analyzed follow-up histology of LGSIL-H cases and compared the follow-up results of LGSIL-H with LGSIL to determine the utility of LGSIL-H category using a single institution’s experience. Study Design: Pap smea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Such cases are referred to as SILs of indeterminate grade in the TBS 2001 manual, but there was not a specific diagnostic category including the cervical smears which exhibit LSIL and ASC-H cytomorphology in the abbreviated versions of TBS 2001 [10,11]. There have been a number of studies focusing on this subset of cases, and many authors believe LSIL/ASC-H should be considered as a distinct diagnostic category [2,3,4,5,6,7,8] in TBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such cases are referred to as SILs of indeterminate grade in the TBS 2001 manual, but there was not a specific diagnostic category including the cervical smears which exhibit LSIL and ASC-H cytomorphology in the abbreviated versions of TBS 2001 [10,11]. There have been a number of studies focusing on this subset of cases, and many authors believe LSIL/ASC-H should be considered as a distinct diagnostic category [2,3,4,5,6,7,8] in TBS.…”
Section: Discussionmentioning
confidence: 99%
“…from 29 to 40.7% [1,5,6,7,8,9,12,13], and a small number of studies showed higher rates of CIN2/CIN3 for LSIL/ASC-H, i.e. from 45 to 61% [2,3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that these intermediate morphological patterns might be better designated with a diagnostic term that better conveys these findings. Many terminologies have been used, such as LSIL, cannot exclude HSIL (LSIL‐H), LSIL cannot rule out high‐grade lesion (LROH), LSIL with ASC‐H , LSIL with rare atypical cells suggestive but not diagnostic of HSIL , LSIL with an additional note alerting the provider to the presence of cells suggestive of HSIL , among others . However, this intermediate category is not part of the TBS 2014 reporting system and its use is discouraged.…”
Section: Introductionmentioning
confidence: 99%
“…Several reported studies have indicated that patients with LROH/LSIL‐H appeared to have an intermediate risk of harbouring or developing high‐grade squamous lesions on biopsy and a different HPV prevalence compared with LSIL and ASC‐H, ranging from 22.8% to 59% of cases . Because of the increased incidence of high‐grade lesions found on histology, comparable to patients with HSIL, it has been proposed that these patients may require a clinical management similar to HSIL diagnosis …”
Section: Introductionmentioning
confidence: 99%